Brand image under threat: How resistance shapes Moroccan consumer engagement and loyalty - BENBARI , Maryem; MOUTANE , Ilyas; NHAILI , Hatim; MESRAR , Asmaa; BHIH , Nabila (Revue Internationale des Sciences de Gestion, 2026)
Consumer resistance or opposition has turned into a crucial element in defining brand engagement and loyalty, particularly in situations where the reputation of the brand is at risk. This research examines how consumers in Morocco respond to brand controversies, cultural differences and behaviors deemed unethical. Building on consumer resistance theory and brand capital theory, the study investigates the emotional, cognitive, and behavioral processes that lead to resistance and guide brand choices. Through a qualitative approach based on semi- structured interviews, the survey detects the main factors of resistance, such as perceived injustice, attacks on autonomy, degradation of loyalty and mismatch with individual or cultural values. The results indicate that resistance erodes the crucial elements of brand capital (loyalty, perceived quality and brand connections), ultimately leading to a withdrawal or overt opposition. The results also highlight the importance of consumer involvement, which can mitigate or strengthen resistance depending on the strength of the pre-existing brand link. By contextualizing consumer responses in the Moroccan socio-cultural framework, the analysis provides insights for brand crisis management and customer relationship approaches in developing markets.